Treatment efficacy of a probiotic preparation for non-alcoholic steatohepatitis: a pilot trial - Manzhalii, Elina; Stremmel, Wolfgang (Journal of digestive diseases, 2017)
OBJECTIVE To evaluate the therapeutic effect of a probiotic cocktail containing Lactobacilli, Bifidobacteria and Streptococcus thermophilus on non-alcoholic steatohepatitis (NASH). METHODS In this open-label trial, 75 patients with NASH fed a low-fat/low-calorie diet were randomly divided into the control group and experimental group, with the latter receiving the probiotic cocktail once daily for 12 weeks. RESULTS All patients were diagnosed with fatty liver by ultrasound examination and had elevated levels of γ-glutamyl transferase (GGT) and alanine aminotransferase (ALT), and slightly increased body mass index (BMI) and cholesterol levels. BMI and serum cholesterol were reduced by the low-fat/low-calorie diet but ALT was not. However, the short-term (12-week) treatment with the probiotic cocktail caused a significant (by >20%) reduction of serum ALT compared with controls, indicating mitigation of inflammation. Accordingly, liver stiffness was decreased in the probiotic-treated group compared with the control group (P < 0.05). Moreover, a more significant decrease in the BMI and serum cholesterol was observed in the probiotic-treated group compared with control (P < 0.05). However, the reduction of GGT as a steatosis marker was insignificant. The composition of stool microbiota in probiotic-treated patients demonstrated a shift towards a normal pattern for all bacterial species examined. No adverse events were observed in any patient during the trial. CONCLUSION Short-term treatment with the probiotic cocktail caused significant improvement of liver inflammation without adverse events and, thus, may represent a promising candidate therapeutic approach for NASH.
Gesehen am 19.09.2017